2006
DOI: 10.1007/s00167-006-0160-4
|View full text |Cite
|
Sign up to set email alerts
|

Hamstring tendons regeneration after ACL reconstruction: an overview

Abstract: Despite the long lasting research the ideal method of reconstructing the ACL has not been found so far. The last year's attention has shifted to the use of the multistrand hamstring tendon grafts. High ultimate tensile load, multiple-bundle replacement that better approximates the anatomy of the normal ACL and low donor site morbidity are the main advantages of this ACL replacement graft. These theoretical advantages have been multiplied when surprisingly studies have shown that semitendinosus and gracilis ten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
25
0
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 44 publications
4
25
0
1
Order By: Relevance
“…If only the ST ST semitendinosus tendon was harvested with an intact G tendon, neotendon developed in 18 (72 %) cases, and then the insertion site was mostly below the joint line but above previous pes anserinus site, in 15 (83.3 %) of the legs. Our ultrasound findings are in agreement with findings from imaging studies in which the regenerated ST tendon seemed to insert more proximally on the gastrocnemius fascia rather than on the tibia, as does the native ST tendon [5,6,[17][18][19][20][21]. This different insertion pattern of the regenerated tendon could explain how it acts mainly as a flexor muscle rather than as a flexor and internal rotator [22][23][24].…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…If only the ST ST semitendinosus tendon was harvested with an intact G tendon, neotendon developed in 18 (72 %) cases, and then the insertion site was mostly below the joint line but above previous pes anserinus site, in 15 (83.3 %) of the legs. Our ultrasound findings are in agreement with findings from imaging studies in which the regenerated ST tendon seemed to insert more proximally on the gastrocnemius fascia rather than on the tibia, as does the native ST tendon [5,6,[17][18][19][20][21]. This different insertion pattern of the regenerated tendon could explain how it acts mainly as a flexor muscle rather than as a flexor and internal rotator [22][23][24].…”
Section: Discussionsupporting
confidence: 89%
“…We agree that the surgical procedure must be as non-traumatic as possible in order to preserve normal vascular anatomy of the harvesting area and the expected regeneration process [18]. Secondly, our study shows that when the G tendon is left intact, the ST tendon regeneration was more successful in 72 % of cases compared to 60 % when the G tendon was harvested in addition.…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…Many research papers have demonstrated the regeneration of the tissues, in the area that provides these autografts [9][10][11][12][13][14][15][16][17].…”
mentioning
confidence: 99%
“…The ST is known to regenerate relatively well after the harvesting, forming a so called neotendon 3 . However, sometimes the regeneration process of the neotendon is disturbed which causes pain, weakness and cramping to the posterior thigh [4][5][6][7][8][9] . The reasons for the compromised healing of the neotendon are not well described in the literature earlier, although the cause for chronic posterior thigh pain might be too early started and rapid progression in postoperative physiotherapy or a new injury to the posterior thigh after harvesting 10 .…”
Section: Introductionmentioning
confidence: 99%